Faktor-Faktor yang Mempengaruhi Minat Menabung Nasabah pada Produk Tabungan iB Siaga - Has, Annisa Muharni (BISMA : Business and Management Journal, 2023)
This study aims to determine what factors influence the initial interest of Bank KB Bukopin customers in saving using the iB Siaga savings product by using the theory of planned behavior, which includes attitudes, subjective norms and perceptions of behavioral control in order to increase the number of customers saving. This type of research is a quantitative approach. The variables used in this study are attitudes, subjective norms, perceptions of behavior control and interest in saving in the iB Siaga savings product. The data sources used are primary and secondary data. Methods of data collection using a questionnaire. The number of samples used was 84 customer respondents who used the iB Siaga savings product. The data analysis technique used is descriptive analysis, validity test, reliability test, classical assumption test, hypothesis test and multiple linear regression test. The results of the study show that (1) the attitude variable has a significant effect on the customer's intention to save in the iB Siaga savings product. (2) the subjective norm variable has a significant effect on the customer's intention to save in the iB Siaga savings product. (3) the perceived behavioral control variable has no significant effect on the customer's intention to save in the iB Siaga savings product. (4) the variables of attitude, subjective norms and perceptions of behavioral control simultaneously influence customers' interest in saving in the iB Siaga savings product